Conditions And Prospects For Development Of Innovation In EU Economies In Light Of The Europe 2020 Strategy; Uwarunkowania i perspektywy rozwoju innowacyjnosći gospodarek Unii Europejskiej w sẃietle Strategii Europa 2020 - Edyta Dworak; Witold Kasperkiewicz (Comparative Economic Research. Central and Eastern Europe, 2013)
The purpose of this paper is to explain the essence of the Europe 2020 Strategy, with particular emphasis on development projects in the field of innovation;to assess the level of innovation in the EU economies in comparison to the U.S., Japan and South Korea, and to describe the conditions for the development of the EU economic area in light of the Strategy program objectives. The paper consists of three parts. The first part outlines the essence and objectives of the Europe 2020 Strategy. The second part contains an analysis of the level of innovativeness of the EU economies compared with U.S., Japan and South Korea. The third part focuses on the conditions and prospects for the development of innovative economies in the European Union. – – Celem opracowania jest wyjasńienie istoty Strategii Europa 2020 ze szczegoĺnym uwzglednieniem projektoẃ rozwojowych w dziedzinie innowacyjnosći, dokonanie oceny poziomu innowacyjnosći gospodarek unijnych na tle USA, Japonii i Korei Płd., a takzė odpowiedzńa pytanie dotyczace warunkoẃ rozwoju innowacyjnosći unijnego obszaru gospodarczego w sẃietle celoẃ programowych Strategii. Opracowanie składa sie z trzech czesći. W czesći pierwszej przedstawione sa istota i załozėnia Strategii Europa 2020. Czesćd́ruga zawiera analize poziomu innowacyjnosći gospodarek Unii Europejskiej w poroẃnaniu z USA, Japonia i Korea Płd. W czesći trzeciej rozwazȧnia koncentruja sie na przedstawieniu uwarunkowaní perspektyw rozwoju innowacyjnosći gospodarek Unii Europejskiej.
Keywords: 330; invention; innovation; innovation gap; knowledge - based economy; R&D activity